Internal vs. external corporate social responsibility at U.S. banks - Brian Bolton (International Journal of Financial Studies, 2020)
This study analyzes the effect that banks' investments in corporate social responsibility (CSR) have on bank performance. I find that banks' investments in CSR have a positive impact on financial performance, measured in terms of both accounting performance and stock market value. However, not all CSR investments are the same. I distinguish between internal CSR and external CSR. This distinction is based on which constituents are most directly affected by the CSR initiatives. Separating bank CSR activities into internally focused and externally focused ones provides evidence on how different constituents value bank CSR activities. I find that CSR-related value creation is primarily a result of banks' external investments and not a result of their internal investments. I also consider how internal and external CSR activities influence bank risk. I find that banks with higher CSR scores are less risky. This is driven by their external CSR investments and not by their internal CSR investments. Banks with a larger gap between internal and external CSR investments have worse performance, lower valuations, and greater risk than banks with a more balanced distribution between internal and external CSR investments. Banks which are committed to long-term structural CSR investments that benefit a broad community of stakeholders are rewarded by the financial markets. Moreover, from a regulatory policy perspective, these same banks are less risky and less likely to contribute to systemic macroeconomic risk.
Keywords: M14; G01; G20; G32; G34; 330; corporate social responsibility; CSR; financial institutions; banks; risk; performance; financial crisis; corporate governance